Deaf users and access to information on Brazilian government websites - Santos, Sylvana Karla da Silva de Lemos (Informação em Pauta, 2020)
Informational practices relate the user's need, how he seeks, retrieves, and accesses information. With the use of Information and Communication Technologies (ICT) the process of searching for information has become more dynamic, which does not mean that it is accessible if we consider the different profiles and behaviors of users, including deaf people. This research identifies Deaf user satisfaction with accessibility to information on Brazilian government websites. The specific objectives of the study are: (1) to know the sociodemographic profile of the Deaf user; (2) investigate the Deaf user information practices related to the Brazilian government websites; (3) identify the factors that impact on accessibility to information on Brazilian government websites; (4) describe the main difficulties related to accessibility in brazilian government websites faced by the Deaf user. The investigation is situated in Information Science in the field of Information Users Studies, in an interdisciplinary way and contemplates concepts of Informatics, Linguistics and Communication. It presents a descriptive characteristic, transversal temporal horizon and approach of mixed methods. The methodological procedures originate from the survey, content analysis and comparative study. The instruments of collect were produced in Libras (Brazilian Sign Language) and applied through interviews and computer tasks with four Deaf teachers, resident in the Federal District, who teaches Libras in higher education institutions. It has been found that participants daily use smartphone and communication applications to send text, image and video. All teachers were able to perform the tasks, but pointed out difficulties in accessing information, mainly due to the excess of text and unknown terms. Deaf teachers suggest increasing to create contents with Libras on the web to contemplate sign language users.